2017
DOI: 10.1080/01612840.2017.1289286
|View full text |Cite
|
Sign up to set email alerts
|

A Life Course Theory Approach to Understanding Eritrean Refugees' Perceptions of Preventive Health Care in the United States

Abstract: Thousands of Eritreans flee their homes each month, embarking on dangerous journeys. With these extreme life experiences in mind, this qualitative study aimed to better understand Eritrean resettled refugees' perceptions of United States (US) preventive health care through the lens of the Life Course Theory. Through secondary thematic analysis of narrative data, two over-arching themes emerged: 1) a thirst for information, understanding and affordable health care and 2) attitudes of gratitude and hope despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For example, communication between health care service providers and patients is of key importance for building trust in health care institutions, where insufficient health literacy and language issues may specifically constitute important barriers in this regard [69]. Additional refugee-related factors such as socio-economic position in the host society, gender roles, lack of adequate information, difficulties in navigating organization of the health care services, and cultural beliefs and practices in regard to health and illness may potentially hamper access to health care utilization [57,65,69,70,71,72,73]. Engagement of the refugee communities in the development of health care policy and delivery, as well as participatory health care research, are suggested to be viable for addressing such barriers to care [69,71,72,74,75].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, communication between health care service providers and patients is of key importance for building trust in health care institutions, where insufficient health literacy and language issues may specifically constitute important barriers in this regard [69]. Additional refugee-related factors such as socio-economic position in the host society, gender roles, lack of adequate information, difficulties in navigating organization of the health care services, and cultural beliefs and practices in regard to health and illness may potentially hamper access to health care utilization [57,65,69,70,71,72,73]. Engagement of the refugee communities in the development of health care policy and delivery, as well as participatory health care research, are suggested to be viable for addressing such barriers to care [69,71,72,74,75].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, community gatherings [57] and involvement in leisure activities [94] were reported to function as protective factors against depressive states and experiences of anxiety. In relation to healthcare, community-based approaches in psychiatry help to address sociocultural barriers to psychiatric care [72] and the quality of health care service delivery [52], resulting in increased access to preventive healthcare and consequent decreases in psychological distress [68,73]. Additionally, a community-based approach in research enables participants to address sensitive issues related to health risk behaviors [84] and emotional experiences, and this in turn results in decreased stress [73] and depression [75].…”
Section: Resultsmentioning
confidence: 99%
“…These patients will seek help in an ED when suffering from an acute problem, as costs will then be covered by the compulsory health insurance. Especially immigrants from different cultural backgrounds are not familiar with preventive care services, such as routine screening, which can detect early oral health problems before they become symptomatic, expensive, and potentially damaging [27][28][29][30][31]. The key problem is that EDs are normally not equipped to provide definitive dental care.…”
Section: Oral Health Of Immigrantsmentioning
confidence: 99%
“…For example, communications between health-care service providers and patients are of key importance for building trust in health-care institutions, where insufficient health literacy and language issues may constitute significant barriers (Lazar et al, 2013). Additional refugeerelated factors, such as socio-economic positions in the host society, gender roles, lack of adequate information, difficulties in navigating the health-care services and cultural beliefs and practices with regard to health and illness may potentially hamper access to health care (Conviser, 2007;Evans, 2011;Lazar et al, 2013;Cheng et al, 2015;Gerber et al, 2017;Pejic et al, 2017;Worabo, 2017). Engaging the refugee communities in the development of health-care policies and their delivery, as well as participatory health-care research, is suggested as a way of removing the barriers to care (Lindgren and Lipson, 2004;Lazar et al, 2013;Cheng et al, 2015;Riggs et al, 2015;Pejic et al, 2017).…”
Section: Previous Researchmentioning
confidence: 99%